Bioscience and the good life - Brassington, Iain (Science, ethics & society., 2012)
The field of biotechnology has provided us with radical revisions and reappraisals of the nature and possibilities of our biological existence. Yet beyond its immediate utility, does a life healthier, longer, or freer from disease make us.